An efficientmethod to determine chemical potential of mixtures in the isothermal and isobaric bulk phase with kineticMonte Carlo simulation. (17th January 2016) - Tan, Shiliang (Johnathan); Do, D. D.; Nicholson, D.
ABSTRACT: A kinetic Monte Carlo (kMC) scheme in the NPT ensemble (constant number of molecules, pressure and temperature) has been developed to determine accurate chemical potentials for all components in a homogeneous mixture. The simulation requires two moves: (1) a displacement move and (2) a volume change move. In the former, the mobility rate of a selected molecule is determined by its interaction with all the other molecules in the system and is moved to a random position within the simulation box, according to the Rosenbluth algorithm, without any rejections (entropic sampling). The volume change move is decided by a comparison between either the instant pressure or the partial average pressure (with long-range correction) and the specified pressure and is carried out much less frequently than the displacement move. We applied this NPT scheme to a number of mixtures in both the gaseous and liquid phases, and show that the derived chemical potentials are accurate and reproducible. The method is recommended for obtaining chemical potentials in mixtures that are required as input in a grand canonical ensemble simulation. Abstract :